Work Engagement Memediasi Job Resources Terhadap Task Performance - Nala Tri Kusuma; Ignatius Soni Kurniawan; Jajuk Herawati (JURNAL MANAJEMEN DAN BISNIS INDONESIA, 2022)
The research aims to test the mediation of work engagement between job resources toward task performance. The method used in this research is quantitaive method with accidental sampling technique. The sampel used in this government employees. The result indicate that job resources has a significant effect to work engagement, work engagement has a significant on task performance, job resources has no significant task performance and the result showed that work engagement mediated between job resources toward task performance